2016
DOI: 10.1002/mds.26505
|View full text |Cite
|
Sign up to set email alerts
|

A cumulative genetic risk score predicts progression in Parkinson's disease

Abstract: We present results linking cumulative genetic risk to a motor outcome in Parkinson's disease. Our findings provide a valuable starting point for future large-scale efforts to map the genetic determinants of phenotypic variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 24 publications
2
44
1
Order By: Relevance
“…All of them found an association of an older age at onset with worse motor and nonmotor performance . Two recently published studies in 336 and 192 patients reported a higher genetic burden to be associated with faster motor and/or cognitive progression . However, the genetic risk score that was used comprised less variants from GWAS analyses than included in our analysis, and the researchers used a different approach defining outcome parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them found an association of an older age at onset with worse motor and nonmotor performance . Two recently published studies in 336 and 192 patients reported a higher genetic burden to be associated with faster motor and/or cognitive progression . However, the genetic risk score that was used comprised less variants from GWAS analyses than included in our analysis, and the researchers used a different approach defining outcome parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] Two recently published studies in 336 and 192 patients reported a higher genetic burden to be associated with faster motor and/or cognitive progression. 31,32 However, the genetic risk score that was used comprised less variants from GWAS analyses than included in our analysis, and the researchers used a different approach defining outcome parameters. Furthermore, it is not reported whether or not patients with pathogenic PD-associated mutations have been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative burden of common GWAS variants has been associated with earlier PD onset and higher rates of motor and cognitive progression . Presuming that common risk loci contribute to familial clustering in non‐Mendelian PD, one would expect cumulative genetic risk score (GRS) to be on average higher in patients with a positive family history.…”
Section: Relationship Between Genetic Risk Age At Onset and Family mentioning
confidence: 99%
“…The concept of polygenic risk score (PRS), however, is increasingly being used to predict treatment outcomes in complex‐genetic disorders. In complex‐genetic PD, cumulative polygenic risk scores were shown to be associated with age at onset and faster motor and cognitive deterioration . Anticipating the possible disease course may help to inform treatment decisions, but the significance of PRS in predicting treatment outcome has to be investigated in prospective, longitudinal studies.…”
Section: Scope Of the Problemmentioning
confidence: 99%